(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
IBL refers to a range of approaches to learning that arebased around processes of self-directed inquiry. Students conduct inquirieswhich are designed to enable them to actively explore questions and problemswithin their discipline. IBL can operate as the design principle for entiremodules and programmes, or can be implemented as discrete activities within alecture-based module.